Social protection, the COVID-19 crisis, and the informal economy: Lessons from relief for comprehensive social protection - Laura Alfers; Florian Juergens-Grant (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper considers the implications of COVID-19 relief measures for the building and extension of comprehensive and universal social protection systems. It highlights three key areas emerging from the crisis, which are likely to affect the shape of social protection systems moving forward. These include the contested meaning of universality, the digitization of social protection systems, and the possibilities for informal worker participation in building a more inclusive social protection. In doing so the paper argues that the terrain of the social protection debate is shifting-it is increasingly uncontroversial that universal social protection is needed and that the state must play a role. However, the more nuanced debates that are emerging across the three areas identified will shape the terrain of whether the form of universal social protection that remains after COVID-19 is a positive and supportive form of inclusion.
Keywords: 330; informal workers; universal social protection; COVID-19 relief; financing; digitization